2014
DOI: 10.4238/2014.june.16.5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the c.1517G>C genetic variant in the XRCC1 gene on pancreatic cancer susceptibility in a Chinese population

Abstract: ABSTRACT. We investigated the influence of the c.1517G>C genetic variant in the X-ray repair complementing group 1 gene (XRCC1) on pancreatic cancer (PC) susceptibility in Chinese patients. A total of 390 PC patients and 392 controls were enrolled in this case-control study. The genotypes of c.1517G>C genetic variants were determined using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. Our findings suggested that the allele and genotype frequencies in PC patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previously c.1517G>C genetic variant of the XRCC1 gene also was reported to be significantly associated with pancreatic cancer in a study conducted by Zhao et al, (2014) They noted that The CC genotype was significantly associated with an increased risk of pancreatic cancer. They reported that C allele may contribute to development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously c.1517G>C genetic variant of the XRCC1 gene also was reported to be significantly associated with pancreatic cancer in a study conducted by Zhao et al, (2014) They noted that The CC genotype was significantly associated with an increased risk of pancreatic cancer. They reported that C allele may contribute to development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to investigate the association between XRCC1 (c.1517G>C) polymorphism and the risk of HCC in Egyptian patients who are chronically infected with HCV. This genetic variant represents a non-synonymous G to C mutation in exon 14 of the XRCC1 gene, resulting in glycine (Gly) to alanine (Ala) amino acid replace-ment (p.Gly506Ala) (Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Two case-control studies on the relationship between c.1517G > C polymorphism and susceptibility to pancreatic cancer were included in our systematic review. Zhao et al [21] and Hou et al [22] reported that the XRCC1 c.1517G > C variant is significantly associated with pancreatic cancer susceptibility in the Chinese population. According to the current evidence-based literature, we thought that there was significant association between XRCC1 gene c.1517G > C polymorphism and pancreatic cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Molecular epidemiological studies have shown that XRCC genes are significantly associated with lung cancer, [6][7][8][9] oral cancer, 10 bladder cancer, [11][12][13] ovarian cancer, 14,15 esophageal cancer, 16 and gastric cancer. [17][18][19][20][21][22][23] Moreover, studies have revealed that XRCC gene polymorphism is highly variable in different ethnic populations. [24][25][26][27][28] Studies have shown that defect in DNA repair mechanism is significantly associated with the increased risk of breast cancer (BC) in females.…”
Section: Introductionmentioning
confidence: 99%